The effect of make-up on the emotions and the perception of beauty (Research, Society and Development, 2021)
A personal image is a key factor in communication and socialization of the individuals and exerts a positive influence on self-esteem when it is aligned with a positive self-image. In light of this, the purpose of this literature review is to explore the effects of makeup on brain activity and the neurobiology of emotions. Makeup is a device used every day by several people, and its use can be regarded as a widespread and long-standing practice that strengthens the self-esteem of many women by providing them with a feeling of security that enhances their image of themselves. It can be inferred that since makeup serves to highlight someone´s beauty, (and bearing in mind that beauty is an all-embracing concept), it may well closely related to the emotions. A number of studies have aimed at exploring our perception of someone wearing makeup, and how this affects our understanding, as well as the procedures involved in its application and its possible effects. In particular, the relationship between makeup, self-esteem, emotions and the brain cells which are involved in emotions and the way which they are expressed may be highlighted.